VISUAL COMMUNICATION MEDIA DESIGN AS A PROMOTIONAL STRATEGY FOR ADI JAYA INTERIOR IN DENPASAR - I Putu Arista Paraditya; Leli Ramdan (Journal of Aesthetics, Design, and Art Management, 2025)
Purpose: Previous promotional activities of Adi Jaya Interior were still carried out conventionally through word-of-mouth communication, which limited their effectiveness. As a professional interior design service provider, the company also lacked a structured visual communication medium. This study aims to design relevant visual communication media to support promotional activities and strengthen brand identity. Research methods: The research employed a qualitative approach using both primary and secondary data, with the design process conducted through three production stages: pre-production, production, and post-production. The outcomes of the design include a new logo, brochure, stationery (envelope, letterhead, business card), billboard, and transportation vehicle branding Findings: Internal evaluation indicates that all media successfully applied visual communication design principles such as balance, hierarchy, unity, as well as appropriate color and typography choices aligned with the company’s character. External evaluation from clients confirmed that the designed media conveyed a modern, neat, and easily recognizable impression. Implications: These media are expected to enhance promotional effectiveness, expand brand exposure, and build public trust in Adi Jaya Interior.